Restless valley revolution, murder, and intrigue in the heart of Central Asia - Shishkin, Philip 1977- (Yale University Press, 2013)
Two revolutions, a massacre of unarmed civilians, a civil war, a drug-smuggling highway, brazen corruption schemes, contract hits, and larger-than-life characters who may be villains ... or heroes ... or possibly both. A gripping, firsthand account of Central Asia's unfolding history from 2005 to the present. Shishkin focuses mainly on Kyrgyzstan and Uzbekistan. Both nations have struggled with the enormous challenges of post-Soviet independent statehood; both have developed into a key smuggling hub for Afghanistan's booming heroin trade